The Usefulness of Corporate Income Tax Accounting: Evidence from Pension Returns - Cussatt, Marc; Demeré, Paul (The Accounting Review, 2023)
ABSTRACT We explore whether income tax accounting (ITA) for pensions provides measurement benefits incremental to U.S. GAAP. We use publicly reported Form 5500 defined-benefit pension expense and funding measures, which are calculated using ITA rules, and contrast them with parallel GAAP amounts. We document that ITA measures are more strongly associated with market value, future cash contributions, the cost of equity capital, and credit ratings than comparable GAAP measures, particularly when ITA better maps to economic fundamentals and when GAAP offers greater managerial discretion. Using intraday returns and disclosure times obtained through a Freedom of Information Act request, we also find that markets quickly react to the release of ITA measures in Form 5500. Our study provides novel empirical tests of theory about the benefits of ITA using actual, not imputed, ITA measures and provides evidence that investors can and do use the unique information in a publicly disclosed tax form. JEL Classifications: H25; J32; M41; M48.